Modernist Bildungsroman and Biology - Kascakova , Janka (Hungarian Journal of English and American Studies, 2021)
Book review: Newman, Daniel Aureliano. Modernist Life Histories: Biological Theory and the Experimental Bildungsroman. Edinburgh: Edinburgh UP, 2019. 234 pages. ISBN 9781474439619. Hb. £80.